Hemostasis in pregnant women with COVID‐19. Issue 2 (16th December 2020) - Ciavarella, Alessandro; Erra, Roberta; Abbattista, Maria; Iurlaro, Enrico; Boscolo‐Anzoletti, Massimo; Ossola, Manuela Wally; Mosca, Fabio; Ferrazzi, Enrico; Peyvandi, Flora; Martinelli, Ida
Abstract : Coagulation parameters investigated in this pilot study were similar in pregnant women with COVID‐19 who were asymptomatic or had mild symptoms, and in pregnant women without COVID‐19 infection.